Distribusi dan Interaksi Tegangan Sisa antar Lubang Setelah Proses Cold Expansion Hole - Wahjudi, Ari; Purnowidodo, Anindito; P, Andika H (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2012)
It is well known that the main cause of a failure of structure is initiated by cracks on a member. A crack may originate easily in a region with high stress concentration. Because in the rivet and the bolt joining method are usual with number of holes, and to reduce the stress concentration, the compressive residual stress is introduced in the region near by the hole. The cold expansion hole technique is used to developed compressive residual on the vicinity of the edge hole. The present study was carried out by the computer simulation based on finite element method to investigate the distribution and interaction residual stress in the region between holes related to the cold expansion hole. The result of the study suggests that the distance between holes influence the state of residual stress and its magnitude. These cause by the deformed material between holes interact each other.Keywords: residual stress distribution, stress interaction, region between holes